The Relationship Between Socio-Economic and Cultural Status and Teenage Marriage in The Work Area Of Campalagian Community Health Center In 2024 - Jamir, A.Fatimah; Yanti, Yuniar Dwi; Hastuty, Dewi; Fitriani, Lina (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Marriage is a physical and spiritual bond between a man and a woman to build a life together, fostering a family. West Sulawesi Province is the region with the highest rate of early marriage in Indonesia. According to the 2020 National Social and National Survey (SUSENAS) data, the rate of early marriage in West Sulawesi reached 10.05 percent. These figures demonstrate that early marriage remains prevalent in Indonesia. Purpose: This study aims to examine the relationship between socioeconomic and cultural factors and adolescent marriage in the working area of the Campalagian Health Center. Methods: An analytic survey with a cross-sectional design was used in this study, conducted in 2024. The population consisted of women of childbearing age (WUS) aged 15–25 years. A total of 87 participants were selected using purposive sampling and the Slovin formula. Data were collected through structured questionnaires and analyzed using the chi-square test with the assistance of SPSS software. Results: The findings showed a significant relationship between socioeconomic status and adolescent marriage (p = 0.000 < 0.05), and between cultural values and adolescent marriage (p = 0.000 < 0.05). Among respondents who married before the age of 20, most had lower socioeconomic backgrounds or were influenced by traditions such as early arranged marriages. Conclusion: There is a significant association between socioeconomic and cultural factors and adolescent marriage in the Campalagian Health Center area. The study recommends that the government strengthen education and advocacy programs to reduce early marriage practices and raise awareness of its long-term health and social impacts.